First person - Nicoleta Baxan (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Nicoleta Baxan is first author on 'Characterization of acute TLR-7 agonist-induced hemorrhagic myocarditis in mice by multi-parametric quantitative cardiac magnetic resonance imaging', published in DMM. Nicoleta conducted the research described in this article while in Dr Susanne Sattler's lab at Imperial College London, UK. She is now an MR Physics Research Associate in the lab of Prof. Lan Zhao at Biological Imaging Centre, Imperial College London, UK, investigating the development of novel multi-parametric cardiac magnetic resonance (CMR) tissue-mapping techniques to make progress in the diagnosis and treatment of heart diseases.